Effect of side chain length and stiffness on the adsorption of methacrylate based polymers - Kırgın, Emre. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2020., 2020)
Polymer thin films provide a multifunctional platform to alter the physical, chemical, and biological properties of a wide variety of substrates. To remove residual stresses and solvents, they are annealed above their glass transition temperature (Tg). Polymer chains are adsorbed to the substrate during annealing and presence of the adsorbed layer causes deviation in physical properties. Earlier work elucidated the kinetics of adsorption, structure of the adsorbed layers, as well as the effect of these layers on the physical properties for the linear polymer chains, the effect of the side chain length and stiffness on the adsorption remained completely unknown. Herein, we have investigated adsorption behavior of methacrylate-based polymers with different side chain length and stiffness on hydrophobic passivated silicon (Si-H) and hydrophilic SiOx surfaces. Thickness and growth kinetics of adsorbed layers are determined using ellipsometry, layer structure is resolved by X-ray reflectivity (XR), and the extent of the competing side reactions are monitored using attenuated total reflectance-infrared spectroscopy (ATR-IR). Increasing side chain length decreased the thickness of the adsorbed layers on both surfaces relative to PMMA. Bulky tertiary butyl groups caused an increase in the thickness of the adsorbed layer on SiH surface but has no impact on the SiOx surface. Introduction of neopentyl group yield the thickest adsorbed layer on SiH surface and restore the strength of segment–substrate interactions on SiOx surface. Isobornyl group, the stiffest side group used in this work, provided the thickest adsorbed layer on SiOx surface. Adsorbed layers on SiH surfaces are represented quite well with single layer model whereas on SiOx a bilayer model was necessary to fit the data. Thermal decomposition reactions at high temperatures compete with the adsorption process and robust crosslinked layers were obtained under these circumstances.
Keywords: Polymers.; Methacrylic acid.